Pengembangan E-Modul Terintegrasi STEM (Science, Technology, Engineering And Mathematics) dengan Bantuan Software 3D Pageflip Professional pada Pokok Bahasan Asam Basa - Hirda Karnia; Maria Erna; Herdini Herdini (Universitas Negeri Padang, 2022)
This research is an innovation in the development of teaching materials that adapt 21st century learning, which focuses on the implementation of the development of science and technology. Therefore can be use to integrate of science technology based learning to improve the quality of individual competencies in accordance with the 2013 curriculum. The purpose is to produce integrated STEM E-modul on Acid Base Material. The research instruments were validation sheets and user response questionnaires. Validation has been assessed by the validator team with aspects of content, language, presentation, STEM and graphics. The trial was conducted at four high schools in Pekanbaru. The results percentage of the validation data considered as very valid. While the percentage of graphic aspects and software utilization considered as very valid. Then the percentage of the teacher response questionnaire considered as very good. The research results from the development of an integrated acid-base STEM e-module with 3D Pageflip Professional show that the e-module developed is feasible and valid to increase the involvement of students active roles, especially to train students scientific attitudes, interests and motivation.